Clinical value of BNP and NT-proBNP for evaluating the cardiac function of patients with chronic renal failure - TANG Li; LIAO Chang-bin; ZHONG Chun-mei (Linchuang shenzangbing zazhi)
Objective To investigate the clinical value of B-type natriuretic peptide(BNP) and N-terminal pro-B type natriuretic peptide(NT-proBNP) for evaluating the cardiac function of patients with chronic renal failure(CRF).Methods 120 inpatients with CRF were chosen.The serum creatinine,BNP,and NT-proBNP concentrations were determined.According to China’s improved MDRD formula,the glomerular filtration rate was calculated.According to K/DOQI guide(2003 edition),the patients were divided into CKD stage 3,4,5(not given dialysis) groups.According to the classification issued NYHA,the patients were classified into NYHA grade Ⅰ,Ⅱ,Ⅲ,and Ⅳ groups.The concentrations of BNP and NT-proBNP in patients with different cardiac functions under the same level of renal function,and those in patients with different renal functions under the same level of cardiac function were compared.Results The blood BNP and NT-proBNP concentrations under the same renal level gradually increased with the increases in NYHA grade[for BNP,(134.00 ± 37.27),(300.00± 22.11),(688.00 ± 141.88),and(1 003.5 ± 185.56) μg/L in NYHA grade Ⅰ,Ⅱ,Ⅲ,and Ⅳ respectively with the CKD stage 3 stage];for NT-proBNP[(214.00 ± 92.63),(896.00 ± 200.73),(1 500.00 ± 761.58),and(25 540.00 ± 4 537.30) μg/L respectively].There was statistically significant difference(P<0.05).The blood BNP concentrations in different renal levels under the same NYHA level had no obvious difference(P>0.05).In NYHA grade Ⅰ,Ⅱ and Ⅲ,the blood NT-proBNP concentrations in CKD stage 3 and 4 stage under the same NYHA level had no obvious difference.As compared with CKD stage 4 and 3,the blood NT-proBNP concentrations in CKD stage 5 increased significantly(P<0.05).In NYHA grade Ⅳ,the concentrations of NT-proBNP in CKD stage 3,4,and 5 were(25 540.00 ± 4 537.30),(25 820.00 ± 3 636.18),and(26 208.00 ± 3 920.68) /ng/L respectively(P>0.05).Conclnsions BNP can be used as a diagnostic marker of cardiac insufficiency for patients in CKD stage 3,4 and 5(not given dialysis).NT-proBNP is greatly influenced by renal function,which can be used to evaluate the function of the heart under the premise of considering the renal function,but it is not recommended to use in the CKD stage 5.